The South American Plains Vizcacha, Lagostomus maximus, as a Valuable Animal Model for Reproductive Studies - Dorfman, Verónica Berta (2016)
The vast majority of our understanding of the mammalianreproductive biology comes from investigations mainlyperformed in mice, rats and humans. However, evidencegathered from non-conventional laboratory models, farm andwild animals strongly suggests that reproductive mechanismsshow a plethora of different strategies among species. Forinstance, studies developed in unconventional rodents suchas guinea pigs and hamsters, that share with humans someendocrine and reproductive characters, have contributed to abetter understanding of human physiology and disease [1,2]. Abetter knowledge on the variety of mechanisms that regulatereproduction could lead to improve early diagnosis, treatment,or novel strategies development to ameliorate fertility andguarantee a successful reproduction. In this letter, we brieflyintroduce Lagostomus maximus, an unconventional rodentwhose neuro-endocrinology and reproduction in general haveattracted significant interest in recent years in view of its unusualreproductive traits.